2018
DOI: 10.1016/j.ccell.2018.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Molecular Analysis of Gastrointestinal Adenocarcinomas

Abstract: Graphical AbstractHighlights d GI adenocarcinomas comprised five molecular subtypes:EBV, MSI, HM-SNV, CIN, and GS SUMMARYWe analyzed 921 adenocarcinomas of the esophagus, stomach, colon, and rectum to examine shared and distinguishing molecular characteristics of gastrointestinal tract adenocarcinomas (GIACs). Hypermutated tumors were distinct regardless of cancer type and comprised those enriched for insertions/deletions, representing microsatellite instability cases with epigenetic silencing of MLH1 in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

29
425
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 439 publications
(477 citation statements)
references
References 99 publications
29
425
0
7
Order By: Relevance
“…Remarkably, the high rate of segmental aUPD in STAD and ESCA suggests higher levels of structural CIN in these cancer types compared to COAD and READ, which agrees with a previous study showing more focal amplification events in the upper than in the lower GI tract . Furthermore, most GI cancers contain aneuploid genomes . Our experimental and computational assessment of the genome ploidy confirmed that highly aneuploid tumors display an increased number of aUPD compared to near‐diploid tumors, affecting both whole chromosomes and segments of chromosomes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Remarkably, the high rate of segmental aUPD in STAD and ESCA suggests higher levels of structural CIN in these cancer types compared to COAD and READ, which agrees with a previous study showing more focal amplification events in the upper than in the lower GI tract . Furthermore, most GI cancers contain aneuploid genomes . Our experimental and computational assessment of the genome ploidy confirmed that highly aneuploid tumors display an increased number of aUPD compared to near‐diploid tumors, affecting both whole chromosomes and segments of chromosomes.…”
Section: Discussionsupporting
confidence: 90%
“…36 Furthermore, most GI cancers contain aneuploid genomes. 37 Our experimental and computational assessment of the genome ploidy confirmed that highly aneuploid tumors display an increased number of aUPD compared to near-diploid tumors, affecting both whole chromosomes and segments of chromosomes. In fact, whole chromosome UPD may originate from pre-or postzygotic chromosome segregation defects.…”
Section: Discussionsupporting
confidence: 55%
“…Our analyses suggest that roughly 20% of all FGFR2 ‐altered GEA have at least one coexisting genomic event predicted to decrease the sensitivity to FGFR2‐directed therapies. Recurrent RTK coamplifications are relatively unique to GEA among tubular gastrointestinal cancers, and our results are consistent with studies of other RTKs of interest . The frequency of coexisting alterations is a cautionary tale for developing FGFR2‐directed therapies, particularly monotherapies, in GEA and suggests a need for comprehensive baseline genomic characterization .…”
Section: Discussionsupporting
confidence: 85%
“…First, EBV‐positive tumors are often biased to men, and MSI‐positive GC typically affects elders . Second, longstanding accumulation of DNA methylations are thought to underlie MSI tumors, suppressing the expression of gene sets including MLH1 …”
Section: Discussionmentioning
confidence: 99%
“…19 Second, longstanding accumulation of DNA methylations are thought to underlie MSI tumors, suppressing the expression of gene sets including MLH1. 19,42 Does any type of gene amplification characterize GCYA? The Cancer Genome Atlas analysis indicated that the amplification of genes related to the RTK signaling pathways are frequently observed in the CIN subtype.…”
Section: Discussionmentioning
confidence: 99%